Influence of air scouring on the performance of a Self Forming Dynamic Membrane BioReactor (SFD MBR) for municipal wastewater treatment. (January 2017) - Salerno, Carlo; Vergine, Pompilio; Berardi, Giovanni; Pollice, Alfieri
Highlights: A SFD MBR operated at 93 L m −2 h −1 effectively treated real municipal wastewater. Continuous mesh air scouring was a key factor for ensuring effective operation. The effluent produced with 20 and 50 μm mesh had similar quality features. The 20 μm mesh had much higher cleaning requirements than the 50 μm mesh. Abstract: The Membrane BioReactor (MBR) is a well-established filtration-based technology for wastewater treatment. Despite the high quality of the effluent produced, one of the main drawbacks of the MBR is membrane fouling. In this context, a possible evolution towards systems having potentially lower installation and operating costs is the Self Forming Dynamic Membrane BioReactor (SFD MBR). Key of this technology is the self-formation of a biological filtering layer on a support of inert material. In this work, a lab-scale aerobic SFD MBR equipped with a nylon mesh was operated at approximately 95 L m −2 h −1 . Two mesh pore sizes (20 and 50 μm) and three air scouring flow rates (150, 250, and 500 mLair min −1 ) were tested at steady state. Under all the tested conditions, the SFD MBR effectively treated real municipal wastewater. The quality of the produced effluent increased for lower mesh size and lower air scouring intensity.